Assessment of Streptococcus Mutans Adhesion to the Surface of Biomimetically-Modified Orthodontic Archwires (2023)
Bacterial adhesion and biofilm formation on the surfaces of dental and orthodontic biomaterials is primary responsible for oral diseases and biomaterial deterioration. A number of alternatives to reduce bacterial adhesion to biomaterials, including surface modification using a variety of techniques, has been proposed. Even though surface modification has demonstrated a reduction in bacterial adhesion, information on surface modification and biomimetics to reduce bacterial adhesion to a surface is scarce. Therefore, the main objective of this work was to assess bacterial adhesion to orthodontic archwires that were modified following a biomimetic approach. The sample consisted of 0.017 x 0.025, 10 mm-long 316L stainless steel and NiTi orthodontic archwire fragments. For soft lithography, a polydimethylsiloxane (PDMS) stamp was obtained after duplicating the surface of Colocasia esculenta (L) Schott leaves. Topography transfer to the archwires was performed using silica sol. Surface hydrophobicity was assessed by contact angle and surface roughness by atomic force microscopy. Bacterial adhesion was evaluated using Streptococcus mutans. The topography of the Colocasia esculenta (L) Schott leaf was successfully transferred to the surface of the archwires. Contact angle and roughness between modified and unmodified archwire surfaces was statistically significant. A statistically significant reduction in Streptococcus mutans adhesion to modified archwires was also observed. © 2020 by the authors.